2019
DOI: 10.1186/s12944-019-1015-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium-enriched Bacillus sp. compounds on growth performance, antioxidant status, and lipid parameters breast meat quality of Chinese Huainan partridge chicks in winter cold stress

Abstract: BackgroundBoth selenium (Se) and probiotic Bacillus regulate the metabolism to help defense clod stress and improve the meat quality in breeding chicks. The purpose of this study was to evaluate the effect of supplemental Se and Bacillus in the form of Se-enriched Bacillus (SECB) on the growth performance, lipid parameters, breast Se and antibiotic levels, and breast meat quality of chicken in winter cold stress.MethodsFive hundred 1-d-old chickens were divided into five groups randomly: Control, inorganic Se,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
2
20
0
2
Order By: Relevance
“…In the present study, BSEO exerted antioxidant activities by improving the activities of GSH-Px and T-AOC on serum. The results of the present study were in agreement with previous findings showed that dietary supplementation with BS or EO significantly increased activity of GSH-Px and T-AOC and gene expression (Bai et al 2017;Yu et al 2018;Yang et al 2019). Similarly, the addition of BS or EO had a positive response on antioxidant activity in serum of duck, goose, quail (Chen et al 2013;Attia et al 2017Attia et al , 2019Abdel-Moneim et al 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, BSEO exerted antioxidant activities by improving the activities of GSH-Px and T-AOC on serum. The results of the present study were in agreement with previous findings showed that dietary supplementation with BS or EO significantly increased activity of GSH-Px and T-AOC and gene expression (Bai et al 2017;Yu et al 2018;Yang et al 2019). Similarly, the addition of BS or EO had a positive response on antioxidant activity in serum of duck, goose, quail (Chen et al 2013;Attia et al 2017Attia et al , 2019Abdel-Moneim et al 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Compared with the control and CTS treatments, Se supplementation from different Se treatments (Na 2 SeO 3 , Se-CTS, and Se-CTS-S) indicated higher GSH-Px activity, GSH content, T-AOC, and mRNA levels of GPx-1 and GPx-4 in vitro and in vivo. These results further demonstrated that Se supplementation could improve the antioxidant function in vitro and in vivo ( Wu et al., 2010 , Fan et al., 2012 , Chen et al., 2017 , Yang et al., 2019 ). Moreover, the antioxidant activity of CTS was significantly higher following Se modification and Se-CTS was a more efficient compound ( Qin et al., 2015 ).…”
Section: Discussionmentioning
confidence: 55%
“…It is noteworthy that the antioxidant properties are one of the most important characteristics of Se compounds, especially regulating effects on antioxidant enzymes ( Khan et al., 2018 , Zoidis et al., 2018 , Yang et al., 2019 ). Compared with the control and CTS treatments, Se supplementation from different Se treatments (Na 2 SeO 3 , Se-CTS, and Se-CTS-S) indicated higher GSH-Px activity, GSH content, T-AOC, and mRNA levels of GPx-1 and GPx-4 in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial composition of the ileal mucous membrane and cecal lumen contents in all groups was determined using the plate method. Salmonella Shigella agar was used for salmonella and MRS agar was used for lactic acid bacteria [3,27]. The assays were repeated three times.…”
Section: Plate Methodsmentioning
confidence: 99%